Traces of Joyful Colors - Cuervo, Germán (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2021)
Biographical account of a Parkinson's patient and his relationship with painting as a therapeutic method. The patient narrates how, through artistic exploration with watercolor painting, he feels an improvement in his mood and a decrease in the tremor of his hand.